Effects of Hydrostatic Parboiling on the Milling Quality of Paddy (cv. Parijata) - Mohanty, S N; Bal, S; Dash, S K; Panda, M K (Journal of Agricultural Engineering, 2002)
Paddy grains at initial moisture contents of 14.8% (d.b.), 20.2% (d.b.) and 26.3% (d.b.) were exposed to soaking at different temperature and pressure levels and steaming at different pressure levels to observe their effects on gelatinisation and milling quality. The temperatures of soak water were 40, 50, 60, 70 and 80degreeC for normal atmospheric soaking conditions. At 70 Cv the pressures of soaking t at 2.0, 4.0 and 6.0 kg/cm² were also studied. For steaming, the pressure levels were kept between 0.5 to 2.5 kg/cm² with an increment of 0.5 kg/cm² . The presence of white bellies was observed to be reduced with increased soaking temperature as well as the duration of soaking. The white bellies were eliminated after 5 hours of soaking at a temperature of 80degreeC. The increase in hydrostatic pressure during soaking resulted in faster elimination of white bellies. The white bellies in steamed samples reduced with increase in initial moisture content, duration of steaming as well as pressure of steaming. Similar trends were observed for the head rice yield. The study suggests that proper gelatinisation and head rice yield could be obtained by either soaking or steaming alone for high moisture paddy. The optimum set of conditions consist of steaming the paddy with initial moisture content of about 25% (db) at a steam pressure of 1.5 kg/cm² for 30 min or 2.0 kg/cm² for 20 min.